Correlation and path analysis for agronomic traits contributing to yield in 30 genotypes of soybean - Anna Satyana Karyawati; ENO SINTHIA VINKY PUSPITANINGRUM (Society for Indonesian Biodiversity, 2021)
Abstract. Karyawati AS, Puspitaningrum ESV. 2021. Correlation and path analysis for agronomic traits contributing to yield in 30 genotypes of soybean. Biodiversitas 22: 1146-1151. To obtain more productive soybean genotypes, it is essential to know the contribution of each agronomic trait to the productivity of soybeans. The purpose of this study was to analyze the correlation and path analysis in thirty genotypes of soybeans (Glycine max (L.) Merrill) for eleven traits. The study was conducted in March-June 2019, in an experimental area located at Agro Techno Park, which belongs to Universitas Brawijaya, Malang, East Java Province, Indonesia. The experimental design was a randomized complete block design with three replications. Analysis of correlation showed that the number of branches, number of filled pods, number of seeds per plant, weight of 100 seeds, and weight of seeds per plant had a positive correlation value to the yield. Path analysis showed that the number of seeds per plant had a high positive, direct effect on the yield. The plant height, number of branches, fresh weight and dry weight had an indirect effect on the yield. Based on the result, the number of seeds per plant can be selected as one of the selection criteria in a soybean breeding program to obtain a high-yield soybean variety.